Design, Synthesis and Disposition Studies of New ISRIB Analogues, Targeting eIF2B, as Potential Candidates for enhancing protein synthesis rate - Abo Alard, Akeel (2021)
Neurodegenerative diseases represent a major cause of dementia, which is predominantly a disease of the elderly, and is characterised by a decline in cognitive functions and memory. All these diseases share a similar aetiology, i.e. the production and accumulation of misfolded proteins in the brain. This results in upregulation of the PERK/eIF2α-P pathway of the unfolded protein response (UPR), which in turn leads to reduction of protein synthesis. A recently discovered chemical inhibitor of the integrated stress response, ISRIB 1, is reported to serve as a neuro-enhancer in healthy rodents and neuro-protectant in models of neurodegenerative and traumatic brain injury. Trans-ISRIB acts downstream of eIF2α-P, by destabilization of the ISR-specific eIF2B–eIF2(αP) complex. This occurs through direct engagement of eIF2Bδ by ISRIB, resulting in allosterically antagonizing the inhibitory effect of phosphorylated eIF2 on eIF2B, thus suppressing the integrated stress response (ISR) and allowing resumption of unstressed protein synthesis. This project aims to design, synthesise and evaluate a library of ISRIB derivatives to scope out the overall SARs as best as possible. In addition, this project also aims to improving knowledge of the molecular target of the ISRIB through design, synthesise and evaluate a novel fluorescent ISRIB derivative in order to nail down the molecular target of this compound. This study reports the design, synthesis and pharmacological results (carried out by Prof. David Ron laboratory) of a set of of ISRIB derivatives, based upon the parent ISRIB molecule. The pharmacological assay was designed to probe the ability of these ligands to allosterically antagonising the inhibitory effect of phosphorylated eIF2 on eIF2B by measuring the fluorescence intensity of the CHOP::GFP reporter. A set of ISRIB analogues were designed and synthesised through modification of different motifs on the prototype ISRIB molecule. These include modifying the nature and position of substituents on the terminal phenyl moieties, investigation of replacing the central cyclohexane ring that joins the O-arylglycolamide side chains, and modification of the glycolamide linkage between the central cyclohexane and distal aryl rings (Figure 1). The rationally designed ISRIB analogues afforded a comprehensive SAR study. Synthesis of ISRIB analogues with para-bromine substitution resulted in the identification of a bromo analogue with potency comparable to ISRIB. Our results also showed that modification of the cyclohexane core ring with a piperidinyl and piperazinyl core rings (heterocycloalkyl) resulted in novel analogues which displayed a potency with only two to three-fold lower than trans-ISRIB. In this project, the O-arylglycolamide moiety was also explored and it was found that repositioning the carboxamide group on the central cyclohexane ring by inverting the amide group resulted in maintaining the activity. Interestingly, the pharmacological results showed that the inversion of carboxamide with tethering the terminal ring to glycolamide linker through six-membered ring displayed a well tolerated result. Considering the SAR data, a set of rigidified analogues that possess chromane, benzodioxane and benzoxazine were designed and synthesised to interrogate ISRIB's interaction with eIF2B. These rigidified analogues allowed the generation of new structure-activity relationships and ultimately afforded a promising analogue, ISRIB analogue with benzoxazine moiety, to be used as s a suitable lead compound for design and synthesis of novel fluorescent ISRIB analogues. The N-H group of benzoxazine provided the anchor point to generate labelled ISRIB derivative 156e, which contains a flexible linker terminated with 5/6-carboxyfluorescein moiety. This labelled ISRIB derivative was used as tracers for the development of direct competitive fluorescence polarisation (FP) binding assay (carried out by Prof. David Ron laboratory). This pharmacological tool was instrumental in demonstrating a direct interaction between ISRIB-type compounds and eIF2B. Furthermore, this project also sought to develop new ISRIB analogues for enhancing the ADME properties, as the current ISRIB molecule has poor aqueous solubility and therefore is not orally bioavailable. ISRIB and other selected analogues (piperidine analogue 103, piperazine analogue 108a and benzoxazine analogue 145) were selected for further in vitro ADME studies (aqueous solubility, Caco-2 permeability, and microsomal stability). These analogues were selected based on reported high potency at eIF2B receptors. The results showed a comparable ADME properties for ISRIB and other selected analogues.